2015
DOI: 10.1007/s00404-015-3629-x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evaluation of medicinal plants used for the treatment of abnormal uterine bleeding by Avicenna

Abstract: Investigation of traditional Iranian medicine literatures can lead to the identification of effective natural medicines for the management of AUB; however, conclusive confirmation of the efficacy and safety of these treatments needs more evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 86 publications
0
20
0
1
Order By: Relevance
“…Herbal medicines have been used to treat menorrhagia for centuries in many cultures (Tansaz et al, 2016). Some of these remedies have been reviewed to generate scientific evidence of their efficacy and safety (Mobli et al, 2015). Although we did not consider any nationality restrictions, three Iranian studies on women with AUB-E testing herbal remedy interventions were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbal medicines have been used to treat menorrhagia for centuries in many cultures (Tansaz et al, 2016). Some of these remedies have been reviewed to generate scientific evidence of their efficacy and safety (Mobli et al, 2015). Although we did not consider any nationality restrictions, three Iranian studies on women with AUB-E testing herbal remedy interventions were found.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended medical treatments for HMB include hormonal drugs, such as oral contraceptives, oral progestins, Levonorgestrel intra-uterine devices and Gn-RH agonists, and non-hormonal drugs, such as NSAIDs and tranexamic acid (Rindfleisch et al, 2015). These treatments have their own side effects and sometimes do not show adequate efficacy (Mobli et al, 2015). Herbal remedies are a component of traditional and folk medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Éjszakai álmából ébredve a betegnek ürítés előtt nem szabad vizet innia, ételt fogyasztania vagy valamilyen színező anyagot, mint például sáfrányt, gránátalmát, szennát ennie-innia, mert ez vörösre vagy sárgára színezné a vizeletét, nem szabad zöldségfélét fogyasztania, mert ez zöld színűvé tenné, vagy keserű anyagokat fogyasztania, mert ez megfeketítené a vizeletét." [8,33,34]. A Kánonban találhatók a hashajtás, a hánytatás javallatai.…”
Section: Néhány Avicenna Zsenialitását Tükröző Tanításunclassified
“…Myrtle has known anti-inflammatory (6,7), antibacterial (8), antiviral (9,10), and antifungal (8,11,12) properties, which makes it a good candidate for the treatment of infectious and inflammatory diseases. According to the ITM resources, myrtle resolves swelling, wounds, and injuries (13); its wound exsiccation capability and tissue enforcement properties may be helpful in the treatment of the rhinosinusitis (14).…”
Section: Introductionmentioning
confidence: 99%